Proteins-Based Circuits in an Intelligent Internet of Bio-Nano Things Network for Molecular Diagnostic of Renal Damage - Nieto-Chaupis, Huber (2021)
It is shown that the accumulation of albumin proteins around the locations of podocytes is rather similar to a R-C (Resistance-Capacitor) circuit. While the electric shielding is not enough to detain the pass of albumin, more than a diffusion phenomenon, it is a problem that is entirely treated as one belonging to the classical electrodynamics. In this manner it was identified that the diffusion constant plays a role as the electrical parameters. The permanent aggregation of albumin proteins creates a capacitance. Therefore the expended power by the R-C circuit is interpreted as the loss of energy of renal glomerulus with implications on the performance and homeostasis of kidney. Thus, the identification of electric unbalance is translated as a signal of Kidney disease. The fact of having a physics-based scenario demands us to propose schemes inside the framework of the Internet of Bio-Nano Things.